Suitability of transbronchial needle aspiration for genotyping peripheral pulmonary tumors - Zuccatosta, Lina; Latini, Letizia; Belleggia, Beatrice; Gonnelli, Francesca; Barbisan, Francesca; Goteri, Gaia; Gasparini, Stefano; Marchetti, Antonio (Frontiers in Medicine, 2023)
Background Transbronchial needle aspiration (TBNA) is a sampling tool that has demonstrated a higher accuracy in the diagnosis of peripheral pulmonary lesions (PPL) compared to other techniques. However, there are no studies investigating the value of TBNA in defining the genotype of peripheral lung cancer. Objective To evaluate the accuracy of TBNA in defining the molecular characteristics of peripheral lung cancer. Methods Consecutive patients who underwent TBNA for the diagnosis of a PPL at the Pulmonary Unit of the Azienda Ospedali Riuniti of Ancona (Italy) between January 2020 and September 2022 were included in the study. TBNA was performed under fluoroscopic guidance and the additional support of an ultrasound miniprobe, with an ultrathin bronchoscope with a flexible 21G needle. Samples were smeared on glass slides for cytological evaluation and flushed in 10% neutral-buffered formalin for cell-blocks. Results 154 patients were enrolled:55 were diagnosed with adenocarcinoma and 21 with squamous cell carcinoma. TBNA correctly diagnosed 43/55 (78.2%) patients with adenocarcinoma and 17/21 (81.0%) patients with squamous cell carcinoma, with a sensitivity of 77.5%. Complete genotyping for guiding targeted therapies was obtained in 52 patients (86.6%). Conclusions TBNA is a valid tool for the diagnosis of PPL, allowing a correct diagnosis and a complete genotyping of the tumors in a considerable proportion of patients.